Single-step hydrothermal synthesis of amine functionalized Ce-MOF for electrochemical water splitting - Muhammad Mukhtar Sirati; Dilshad Hussain; Khalid Mahmood; Adeel Hussain Chughtai; Muhammad Yousaf-Ur-Rehman; Wasif Mahmood Ahmad Malik; Sultan Alomairy; Samia ben Ahmed; M. S. Al-Buriahi; Muhammad Naeem Ashiq (Journal of Taibah University for Science, 2022)
Electrochemical water splitting is a well-sought method for the production of renewable energy due to its low cost, high efficiency, ease of operation, availability of a variety of catalysts, and green approach. In this research, an amine-functionalized Ce-MOF loaded on nickel foam (NF) presented as Ce-MOF-NH2/NF electrocatalyst is prepared by a simple hydrothermal method. Prepared material is characterized by X-ray diffraction (XRD), energy-dispersive spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and atomic force microscopy (AFM) to confirm morphological and structural properties. The synthesized catalyst is used for electrochemical OER in a 1M KOH solution. Ce-MOF-NH2/NF demonstrated onset potential, Tafel slope, and overpotential of 1.49 V, 69 mV/dec, and 328 mV, respectively. For comparison, Ce-MOF is also prepared and employed for OER under the same conditions and it exhibited onset potential, Tafel slope, and overpotential 1.5 V, 89 mV/dec, and 348 mV, indicating the superior performance of functionalized MOF. The obtained results reveal the promising overpotential of the Ce-MOF-NH2/NF -based electrocatalyst for green energy production via electrochemical water splitting.